KETERAMPILAN BERPIKIR KRITIS MAHASISWA MATA KULIAH EKOLOGI TUMBUHAN MENGGUNAKAN MODEL PEMBELAJARAN INKUIRI - Ayatusa ’adah, Ayatusa ’adah (Universitas Islam Balitar, 2018)
The purpose of this study is to describe students' critical thinking skills in Plant Ecology courses through inquiry learning. This type of research is a quantitative descriptive research with one group pretest-posttest research design (single group design with pretest-posttest). Data collection techniques used pretest and posttest to measure students' critical thinking skills in understanding during learning. Research data on critical thinking skills from the pretest and posttest were analyzed by calculating the N-gain value. N-gain results indicate that the use of inquiry models can improve students' critical thinking skills. Students ’ posttest data were analyzed descriptively to describe students' critical thinking skills through inquiry learning. The highest average score on the first indicator, which is focusing on questions,gotscore of 73.64, in the criteria of sufficient. The lowest average score is found in two indicators, namely the indicator asking and answering questions and the indicator considering whether the source is reliable or not. Both indicators got a score of 70 in the criteria of sufficient. On average all indicators of critical thinking skills of students got a score of 71.27 in the criteria of sufficient. The conclusion is that the Inquiry learning is able to improve students' critical thinking skills in the medium criteria.